Research coaching: enhancing supervisor’s leader role efficacy - Pinto, Paula (2021)
Supervisors’ leader role efficacy is essential to support PhD students in the transference of both research and transferable skills developed during their doctoral programs, into their future jobs. At Rev UIIPS. 2019; 7(2): 68-7169the same time, these leader role efficacy competences will be translated into a more motivated and productive research team. Coaching will facilitate the leader role efficacy development of group leaders and supervisors. This paper reviews the concept of coaching and mentoring; highlights the main aims of coaching, and the fundamental coaching skills the supervisor may use in facilitating students and team members evolution. The paper finalizes presenting the aims of Transpeer project, a transnational skills programme to enhance the employability of researchers. Development of coaching skills in researchers, and follow up of their application in research environment, will permit to build more evidence on the benefits of research coaching, and its future application.